A score to map the lateral nonprimary motor area: Multispectrum intrinsic brain activity versus cortical stimulation. (15th October 2019) - Neshige, Shuichiro; Kobayashi, Katsuya; Matsuhashi, Masao; Togo, Masaya; Sakamoto, Mitsuhiro; Shimotake, Akihiro; Hitomi, Takefumi; Kikuchi, Takayuki; Yoshida, Kazumichi; Kunieda, Takeharu; Matsumoto, Riki; Maruyama, Hirofumi; et al.
Abstract: Objective: Multispectrum electrocorticographic components are critical for mapping the nonprimary motor area (NPMA). The objective of this study was to derive and validate a reliable scoring system for electrocorticography‐based NPMA mapping (NPMA score) to replace electrical cortical stimulation (ECS) during brain surgery. Methods: We analyzed 14 consecutive epilepsy patients with subdural electrodes implanted in the frontal lobe at Kyoto University Hospital. The NPMA score was retrospectively derived from multivariate analysis in the derivation group (patients = 7, electrodes = 713, during 2010‐2013) and validated in the validation group (patients = 7, electrodes = 772, during 2014‐2017). We assessed the accuracy and reliability of the score relative to ECS in determining the NPMA and predicting postoperative functional outcomes. Results: Multivariate analysis in the derivation group led to an 8‐point score for predicting ECS‐based NPMA (1 point for anatomical localization of the electrode and 1 or 2 points for movement‐related electrocorticographic components regardless of somatotopy in very slow cortical potential shifts [<0.5 Hz], 40‐80–Hz band power increase, and 8‐24–Hz band power decrease), which was validated in the validation group. The area under the receiver operating characteristic curve (AUC) was 0.89 in the derivation group. Good prediction (specificity = 94%, sensitivity = 100%) and discrimination (AUC = 0.87) were reproduced in the validation group. Overall, higher NPMA scores identified 2 patients with postoperative deficits after frontal lobe resection. Significance: The NPMA score is reliable for NPMA mapping, potentially replacing ECS. It is a potential prognostic marker for postoperative functional deficits.